(untitled) (Singaporean Journal of Business Economics and Management, 2018)
The purpose of this paper is to conceptualize temporary organizing as a practopoietic system. We critically review the current conceptualizations of projects; from the traditional project management perspective, and the temporary organization perspective using a systems approach. By juxtaposing the characteristics of the project with a system, we argue that traditional project management is akin to an autopoietic system while temporary organizations may be conceptualized as an allopoietic system. However, these conceptualizations are inadequate to explain the dynamics of the project- the internal workings and its interaction with the environment, as well as the complexity associated in such dynamics. Hence, we reiterate the need to consider the emerging conceptualization of projects as temporary organizing. We position temporary organizing as a practopoietic system that sufficiently explains the dynamics of project within itself, and with the environment while considering the complexity associated with such arrangements.